ASSOCIATION BETWEEN SMOKING STATUS AND DIAGNOSED HEART DISEASE AMONG OLDER ADULTS IN INDONESIA: EVIDENCE FROM THE 2023 NATIONAL HEALTH SURVEY - Yuni Asri; Dian Pitaloka Priasmoro; Sasmiyanto Sasmiyanto (BRIN - Badan Riset dan Inovasi Nasional, 2026)
Heart disease remains a leading contributor to illness and mortality among older adults globally, including in Indonesia. Although smoking is a well-established cardiovascular risk factor, limited national evidence has explored its relationship with heart disease among the Indonesian elderly. This study utilized data from 97,339 adults aged ≥60 years obtained from the 2023 Indonesia Health Survey (Survei Kesehatan Indonesia/SKI) to examine the association between smoking status and physician-diagnosed heart disease, considering various sociodemographic factors. Key variables included age, sex, education, marital status, place of residence, employment, and smoking behavior. Weighted bivariate analyses were conducted using chi-square tests to account for the complex survey design. The overall prevalence of heart disease was 3.5%. Significant associations (p < 0.05) were observed across all sociodemographic characteristics, including smoking status. Interestingly, heart disease prevalence was higher among non-smokers (2.6%) than among smokers (0.9%), which may suggest reverse causality or smoking cessation following diagnosis. These findings emphasize the influence of sociodemographic and behavioral factors on cardiovascular health among older Indonesians. Longitudinal research is needed to better understand the causal mechanisms underlying these associations, particularly regarding smoking behavior.